Modern approaches to vaccines interchangeability - I. I. Snegireva; K. E. Zatolochina; M. A. Darmostukova; R. N. Alyautdin; B. K. Romanov (Регуляторные исследования и экспертиза лекарственных средств)
Research findings demonstrate the possibility of replacing the vaccines, when used in accordance with the recommended dosage and administration schedule specified by the manufacturer. Control and regulatory authorities in many countries publish recommendations on how to proceed in case of the need to replace a vaccine with a similar one. However, in Russia there are no special normative documents regulating interchangeability of vaccines. It is necessary to define the concept of «interchangeability» of a vaccine as «changeability» and extend it to the possibility of continuing immunization course in a specific patient using a drug from a different manufacturer and the possibility of using vaccines with similar therapeutic indications produced by various manufacturers.